Home Background and Classroom Interaction as Correlates of Basic Science Students’ Achievement in Upper Basic Schools in Nasarawa State, Nigeria - Samuel, Ruth Iwanger (International Journal of Current Innovations in Advanced Research, 2023)
This study examined the influence of home background and classroom interaction as correlates of students’ academic achievement in Basic Science. Two research hypothesis were tested at 0.05 level of significance. A simple survey design was adopted for the study. Stratified random sampling technique was used to select 200 JSS II students drawn from five public upper basic schools in Nasarawa West Senatorial District, Nasarawa State, Nigeria. Three instruments namely; Home Background Questionnaire for Students (HOBAS), Basic Science Observation Schedule (BSOS) and Classroom Interaction Questionnaire (CIQ) were used for data collection. The instruments were trial tested and the reliability indices of 0.79, 0.81 and 0.82 respectively were determined using Cronbach Alpha formula. The data collected were analysed using Simple Regression and Bi-variate Analysis of Variance (ANOVA). It was recommended that parents should give attention to their children and teachers should dwell more on classroom interaction so as to boost students’ participation levels and help them in the study of Basic Science, given its relevance to Science and Technology development.